INTERRELATION BETWEEN PROTEINS OF IN-FLAMMATION’s ACUTE PHASE AT BURN DISEASE - Netyukhaylo, L.G. (World of Medicine and Biology, 2012)
The increase of level of haptoglobin and activity of CPU indicates on strengthening of proteometabolism at EBD. It is set the method of correlative analysis, that exists close intercommunication between a haptoglobin and CPU.
Keywords: burn desease; haptoglobin; ceruloplazmin